Students’ Errors in Compiling Geometric Proof of Gender: A Gender Comparative Study - Hendra Susanto; M. Ikhsan; Marwan Marwan (Proceedings of AICS - Social Sciences, 2018)
Mathematical proofing ability is important to learn because it is very influential on the ability of mathematics. The low ability of mathematical proofing is still a problem that is often encountered. Therefore, the low capability of the evidence needs to be explored to know the root of the more detailed problems to be used as initial data so that the solution becomes more precise and effective. Some researchers claim that gender differences also affect mathematical skills. This study aimed to determine the errors and causes in the proof of geometry regarding gender differences. This research was qualitative descriptive research conducted in the Department of Mathematics Education Faculty of Teacher Training and Education, Syiah Kuala University with subject consisting of male and female students. Techniques of collecting data were done through tests and interviews. Data analysis was done based on Miles and Huberman stages, namely data collection, data reduction, data presentation, and conclusions. The error data compiling the geometry proof was analyzed based on Newmann Error Analysis (NEA). The results showed that: 1) mistakes made by male students tend to Process Skill Error; 2) mistakes made by female students tend to Transformation Error; 3) the cause of errors due to the lack of understanding of the concepts (definition, theorem, illustrations, and usefulness) of the students, the lack of logical knowledge and the structure of the method of proof (the way of conclusion either direct or indirect evidence) limitations of language and notation, and lack of care in the settlement procedure.Keywords: students’ errors, geometric proof, gender differences.